The Potency of Soursop Leaf Extracts for the Treatment of Acne Skin - Hanifa Nurusita Wardani (Global Health Science Group, 2020)
Acne is a skin disease that mostly occurs in teenager aged 16-19 years to adult aged 30 years. Acne is generally caused by the growth of Propionibacterium acnes, Staphylococcus aureus, and Staphylococcus epidermidis. Anti-acne drugs usually contained synthetic antibiotics such as erythromycin and clindamycin, which can cause irritation, resistance, organ damage, and even immunohipersensitivity. Therefore we need alternative ingredients that are easy to find and can treat acne, such as soursop leaves. The aim was to analyze the potency of soursop leaf extracts for the treatment of acne skin. The literature review was conducting using reference sources from 24 articles by literature searching on Google Scholar and NCBI that were published in range of year 2005-2020. The keywords are used literature searching acne vulgaris, soursop leaves, propionibacterium acnes, staphylococcus aureus, and staphylococcus epidermidis. The literature which has been collected were analyzed by systematic literature review which include collecting, evaluating, and development of the research that focus on a particular topic. Analysis of various articels that it is known that soursop leaves contain antibacterial compounds such as flavonoids, alkaloids, saponins, tannins, steroids and terpenoids can be used as anti-acne drugs.